Respuesta :

Answer:

(y+2) = (1/3)(x-1)  

Answer in point-slope form, you can rearrange this into the form which you need.

Step-by-step explanation:

recall that the general point-slope form of a linear equation looks like :

(y - y₁) = m(x - x₁)

where m is the slope and (x₁,y₁) is any point on the line

here we are given m = 1/3 and (x₁,y₁)=(1,-2)

simply substitute this info into the general equation above

(y - y₁) = m(x - x₁)

(y - (-2) ) = (1/3)(x - 1)

(y+2) = (1/3)(x-1)  Answer in point-slope form, you can rearrange this into the form which you need.

Answer:

x-3y-7=0

Step-by-step explanation: